A tale of two metals: Biofortification of rice grains with iron and zinc - Wairich, Andriele; Ricachenevsky, Felipe K.; Lee, Sichul (Frontiers in Plant Science, 2022)
Iron (Fe) and zinc (Zn) are essential micronutrients needed by virtually all living organisms, including plants and humans, for proper growth and development. Due to its capacity to easily exchange electrons, Fe is important for electron transport in mitochondria and chloroplasts. Fe is also necessary for chlorophyll synthesis. Zn is a cofactor for several proteins, including Zn-finger transcription factors and redox metabolism enzymes such as copper/Zn superoxide dismutases. In humans, Fe participates in oxygen transport, electron transport, and cell division while Zn is involved in nucleic acid metabolism, apoptosis, immunity, and reproduction. Rice (Oryza sativa L.) is one of the major staple food crops, feeding over half of the world’s population. However, Fe and Zn concentrations are low in rice grains, especially in the endosperm, which is consumed as white rice. Populations relying heavily on rice and other cereals are prone to Fe and Zn deficiency. One of the most cost-effective solutions to this problem is biofortification, which increases the nutritional value of crops, mainly in their edible organs, without yield reductions. In recent years, several approaches were applied to enhance the accumulation of Fe and Zn in rice seeds, especially in the endosperm. Here, we summarize these attempts involving transgenics and mutant lines which resulted in Fe and/or Zn biofortification in rice grains. We review rice plant manipulations using ferritin genes; metal transporters; changes in the nicotianamine/phytosiderophore pathway (including biosynthetic genes and transporters); regulators of Fe deficiency responses; and other mutants/overexpressing lines used in gene characterization that resulted in Fe/Zn concentration changes in seeds. This review also discusses research gaps and proposes possible future directions that could be important to increase the concentration and bioavailability of Fe and Zn in rice seeds without the accumulation of deleterious elements. We also emphasize the need for a better understanding of metal homeostasis in rice, the importance of evaluating yield components of plants containing transgenes/mutations under field conditions, and the potential of identifying genes that can be manipulated by gene editing and other non-transgenic approaches.